Stay curious : how questions and doubts can save your faith - O'Brien, Stephanie Williams (Fortress Press, 2019)
Most of us are going through the motions when it comes to faith, either believing we've found all the relevant answers to life's questions or believing none can be found. We shy away from our deepest questions about God because we fear the uncertainty on the other side. But when we make certainty and correct belief the end goal of faith, we miss out on the chance to know God more deeply and to participate in God's work in the world. Pastor Steph shows us how to lean into our questions and embrace a life of curiosity. Taking Jesus's life as a model, we can confront our fears, be set free from our anxiety, ask new questions, and live into an adventurous life of curiosity. After all, Jesus was a question man, not an answer man. Our questions, and even our doubts, can push us closer to a God we can actually believe in--rather than further from a God we think we can contain. In Stay Curious, Pastor Steph walks readers through common obstacles and road blocks to curiosity, and offers practical strategies for embracing even the most intimidating questions.